Recurrence Rate and Associated Factors of Primary Fallopian Tube Carcinoma in the South of Vietnam - Tuan Vo; Duy Nguyen; Thang Ho; Hoang Tran; Dat Nguyen; Thuong Bui; Thinh Cao; Brian Vo (Wolters Kluwer Medknow Publications, 2024)
Objectives: This study aimed to determine the recurrence rate and related risk factors of primary fallopian tube cancer (PFTC). Materials and Methods: We conducted a retrospective study of 47 patients with histopathological diagnosis of PFTC treated at Tu Du Hospital between January 1, 2015, and July 31, 2022. The cumulative recurrence rate was estimated using the life table method, and recurrence-associated factors were determined using the Log-rank test and Cox proportional hazard model. Results: The median follow-up period was 40 months (range, 7-96 months). Eight patients (17.0%) experienced recurrence. The cumulative recurrence rate of PFTC patients at 12 months was 4.4% (95% confidence interval [95% CI]: 1.12-16.45), at 24 months was 9.1% (95% CI: 3.52-22.5), at 36 months was 14.9% (95% CI: 6.92-30.41), at 48 months was 19.3% (95% CI: 9.35-37.24), and at 60 months was 25.7% (95% CI: 12.68-47.88). A higher recurrence rate was significantly associated with elevated pretreatment CA 125 level (<35 U/mL vs. ≥35 U/mL, hazards ratio [HR] = 36.9, 95% CI: 1.47-921.37), advanced FIGO stages (Stage I-II vs. stages III, HR = 6.61, 95% CI: 1.18-36.93), and suboptimal debulking surgery (residual disease ≤1 cm vs. residual disease >1 cm, HR = 7.52, 95% CI: 1.47-38.49). Conclusion: The overall recurrence rate of PFTC patients in Southern Vietnam was 17.0%. Appropriate follow-up strategies for patients with high-risk factors are needed for early detection and management of recurrence.